PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Ani Sagita Sofi, 15.05.52.0303; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2019)
This research is a study that examines the effect of Corporate Social Responsibility and Good Corporate Governance on Firm Value with the perspective of stakeholder theory and agency theory. The population in this study are manufacturing companies listed on the Stock Exchange in the period 2015-2017. The sample method used in this study was purposive sampling, so the samples obtained were 339 manufacturing companies. In the mechanism of Good Corporate Governance it is divided into three variables, namely independent commissioners, board of directors, and audit committees. In this study the value of the company is dependent on two measurements of formulas namely, PBV and Tobin’s Q and uses company size control variables and leverage. Data analysis using descriptive qualitative with the help of the SPSS 20.00 program. The results of this study indicate that the two independent variables in this study are sensitive to the measurement of firm value. And four other variables in this study have the same results on PBV and Tobin’s Q.